How Paid Plastic-Bag Affect Customer Satisfaction: The Moderating Effect of Sustainable Green Leadership in Pontianak - Wahyudi, Hijrah; Mardiyati, Mardiyati (Universitas Muhammadiyah Pontianak, 2025)
This study analyzes the influence of paid plastic bag policies on consumer satisfaction, moderated by sustainable green leadership in Pontianak, Indonesia. Using quantitative methods with 100 respondents across five districts, data were analyzed through moderated regression (MRA). Results indicate the policy significantly affects satisfaction (p<0.001), with green leadership strengthening this relationship (R²=0.199). The interaction effect shows effective green leadership can mitigate potential negative consumer responses. These findings contribute to environmental policy implementation literature by demonstrating how leadership quality enhances policy acceptance. Practical implications suggest retailers should implement complementary green initiatives alongside plastic bag fees, while policymakers should promote sustainable leadership training to facilitate smoother policy transitions and increase consumer buy-in for environmental measures.